2006
DOI: 10.1093/ptj/86.8.1075
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Function and 3-Dimensional Scapular Kinematics in People With and Without Shoulder Impingement Syndrome

Abstract: Background and Purpose. Several factors such as posture, muscle force, range of motion, and scapular dysfunction are commonly believed to contribute to shoulder impingement. The purpose of this study was to compare 3-dimensional scapular kinematics, shoulder range of motion, shoulder muscle force, and posture in subjects with and without primary shoulder impingement syndrome. Subjects. Forty-five subjects with impingement syndrome were recruited and compared with 45 subjects without known pathology or impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
162
1
16

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 393 publications
(211 citation statements)
references
References 53 publications
6
162
1
16
Order By: Relevance
“…If thoracic or lumbar position is addressed initially, then body posture is not relevant; however, because the monitoring of specific thoracic or lumbar position may be difficult for patients during functional tasks, home exercise, or postural programs, then the simple use of body posture may be more achievable for some patients. Given that shoulder pain is associated with either scapular upward or downward rotation [4,11,12,14,20,22,24,25], anterior or posterior tilt [4,5,8,9,[11][12][13][14]16], and medial or lateral translation [9,20,22], then individual patient presentations will guide the selection of body posture. Slouched sitting posture also can decrease glenohumeral range of motion in comparison to neutral sitting in participants with shoulder pain [27,55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If thoracic or lumbar position is addressed initially, then body posture is not relevant; however, because the monitoring of specific thoracic or lumbar position may be difficult for patients during functional tasks, home exercise, or postural programs, then the simple use of body posture may be more achievable for some patients. Given that shoulder pain is associated with either scapular upward or downward rotation [4,11,12,14,20,22,24,25], anterior or posterior tilt [4,5,8,9,[11][12][13][14]16], and medial or lateral translation [9,20,22], then individual patient presentations will guide the selection of body posture. Slouched sitting posture also can decrease glenohumeral range of motion in comparison to neutral sitting in participants with shoulder pain [27,55].…”
Section: Discussionmentioning
confidence: 99%
“…Scapular orientation is considered a primary influence in the development and maintenance of shoulder pain [1,2]. Although it is acknowledged that shoulder pain may be multifactorial, a majority of cross-sectional studies demonstrate a significant difference between symptomatic and asymptomatic groups [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] for scapular orientation in diverse conditions such as spinal cord injury [18], after breast cancer treatment [16], chronic obstructive pulmonary disease [19], rotator cuff tendinopathies [13,15], glenohumeral or acromioclavicular osteoarthritis [13,20], adhesive capsulitis [13], internal impingement [14], and multidirectional instability [12]. In addition, a number of longitudinal studies have demonstrated that scapular orientation or dyskinesis assessed under load can be predictive of shoulder pain [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle weakness and muscle imbalance can cause impingement of the shoulder joint syndrome, therefore, evaluation of the ratio of antagonist-agonist of the scapulothoracic muscle on one side can help diagnose and treat [2,8,[22][23][24]. To measure the elevation to depression ratio of the scapula, the upper trapezius muscle was considered for elevation and the lower trapezius for depression [15].…”
Section: Methodsmentioning
confidence: 99%
“…Joint stability, defined as the ability of a joint to resist dislocation, is essential for proper joint function (Hall 2003). Proper scapular kinematics (upward rotation, posterior tipping and lateral rotation) during upper limb elevation is important in maintaining GHJ stability (Itoi et al, 1992;Matias and Pascoal, 2006;Struyf et al, 2011) as well as preventing injuries (Brewer et al, 1986;Ludewig and Cook, 2000;Graichen et al, 2001;McClure et al, 2006). After an anterior GHJ dislocation, injured passive joint stabilizers may not be able to provide sufficient mechanical stabilization to maintain the humeral head within the glenoid cavity (Turkel et al, 1981;Itoi et al, 1996;Brenneke et al, 2000;von Eisenhart-Rothe et al, 2002).…”
Section: Introductionmentioning
confidence: 99%